Correspondence: Seán T. Ó Ceallaigh (1934)
Correspondence while Vice-President of the Executive Council (Mar. 1932- Dec. 1937) and Minister for Local Government (Mar. 1932- Sept. 1939).
Letter from Paschal Robinson thanking Ó Ceallaigh for an invitation to diner; from Liam O’ B. regarding the election of the presidency of [Galway] college; and general letter from Lord Granard.